Applying cost–benefit analysis to the economic evaluation of a tram-train system: Evidence from Brescia (Italy). (March 2023) - De Aloe, Maria; Ventura, Roberto; Bonera, Michela; Barabino, Benedetto; Maternini, Giulio
Abstract: Implementation of mass rapid transit systems can be quite expensive in mid-sized cities. Technology can help make existing surface rail vehicle-based transit systems interoperable, limiting the investments required for infrastructure. Tram-Train (TT) may be a viable solution because it can integrate the features of railway and tramway systems using specifically tailored light railway vehicles. Although TT is a well-known system, the related literature is still poor and mainly focuses on the qualitative description of general features, technical and organisational issues, and experiments of some components. Specifically, a detailed analysis of economic evaluations of the implementation of a TT system in a mid-sized city is missing from the research results. This study fills this gap by applying a cost–benefit analysis to Brescia (Italy). The results show the potential viability of an innovative interoperable transport system in this city. These outcomes are very useful as they represent the first empirical evidence evaluating the economic feasibility of a TT, as far as the authors know. Therefore, this study may help provide indications for policy makers and transit experts as a benchmark tool for the scientific community for the application of a TT in a city.